Layer-number dependent electrical and optical properties of transparent conductive RuO2 nanosheets films. (3rd January 2020) - Kim, Se Yun; Shin, Weon Ho; Roh, Jong Wook
Sheet resistance reduction in the transparent conducting electrodes is a very important issue for the application in flexible electronics and optoelectronics. Herein, the layer-dependent electrical and optical properties of RuO2 nanosheets films have been investigated for the application of the flexible transparent conducting electrodes due to their superior optical properties. The sheet resistance abruptly decreased with increasing the number of coating layers. Then the sheet resistance was almost constant after optimum point. In contrast, optical transmittance monotonically decreased with the increase of coating more layers. And, optical haze, another important optical property, did not show significant degradation despite an increase of numbers of RuO2 nanosheets coating layers. This result means the optimum point should be considered when the flexible transparent conducting electrodes are fabricated using nanosheets.